Can the Second and Fourth Finger (2D:4D) Ratio Guide Physicians in Choosing Internal Medicine or Surgical Branch? - Akkoc, Ramazan Fazil; Aksu, Feyza; Horoz, Mert Ali; Bahceci, Nazlican; Hayaloglu, Zeynep; Servi, Refik (Soc Chilena Anatomia, 2023)
This study investigates the relationship between the second and fourth finger ratio (2D:4D), physicians' propensity to choose an internal or surgical branch, and sex differences. On a voluntary basis, 177 physicians working in Elazig, 122 men and 55 women were enrolled in the study. Their hands were measured for 2D and 4D lengths, and the 2D:4D ratio was computed. In female doctors, the left hand's 2D:4D ratio is 1.01, compared to the right hand's 1.00. Male doctors' right 2D:4D ratio is 0.99, while their left 2D:4D ratio is 1.00. Male physicians' 2D:4D ratios were different from those of men in the general population, whereas female physicians' 2D:4D ratios were comparable to those of women in the general population. As a result, this study was the first to examine the relationship between the ratio of the second and fourth fingers (2D:4D), physicians' tendency to choose an internal medicine or surgical branch, and sex differences. While the 2D:4D ratio was higher than 0.98 in all physicians, it was low in women who disliked their profession and branch. Since there aren't many studies on this subject, data from in-depth studies that will be conducted in the future will help physicians who choose internal medicine and surgery make more informed decisions.
¿Puede la proporción del Segundo y Cuarto Dedo (2D:4D) Guiar a los Médicos en la Elección de Medicina Interna o Rama Quirúrgica?
Keywords: 2D; 4D ratio; Digit ratio; Physician; Anthropometry